(untitled) (Journal of Science and Technology, 2016)
This paper takes a look at the effect of power factor correction on the energy consumption in an industry. The use of static capacitors to achieve significant improvement in energy conservation in some industries in Kumasi has been studied. It is estimated that on the average static capacitors can be used to save 20% on industrial electricity bills. The capital recovery period is less than two years for most of the industries studied.